How to ace in biochemistry and molecular medicine - Wan Mohamad Zain, Wan Nor I’zzah; Abd Muid, Suhaila; Muhamad, Mudiana; Khan, Jesmine (Faculty of Medicine, 2023)
On the 4th of July 2023, the Department of Biochemistry and Molecular Medicine (BMM) organized a seminar entitled How to Ace in Biochemistry and Molecular Medicine. The seminar was attended by all Year 1 UiTM medical students (MBBS 240) and held in Auditorium 1, Faculty of Medicine, UiTM Sungai Buloh Campus. It was a half-day seminar consisting of a series of talks by an invited Professor of Biochemistry with an MBBS degree and vast experience teaching the subject, two lecturers from the department, and one alumnus of the UiTM medical graduate.